2014
DOI: 10.4028/www.scientific.net/amm.602-605.361
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study on Force of PDC Cutter Breaking Rock

Abstract: Because the anisotropy of shale formation should result in that wellbore deviations is unpredictable, the bit-rock interaction should be fully lucubrated in order to eliminate this problem. The impact of shale rock anisotropy and the cutting velocity on the load of PDC cutter wasn’t considered by the existing cutter-rock interaction models. On the basis of experiments of cutting shale with PDC cutter, using the stress tensor analysis theory, the relationship between the shale rock anisotropy and the cutter’s f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 7 publications
0
12
0
Order By: Relevance
“…Appl et al [6] developed a new cutter wear model from the cutting experiments. Wang et al [7] established a new cutter-rock interaction model on the basis of experiments of cutting shale with PDC cutter. Kris [8] tested four different batches of PDC under monotonic and cyclic loadings, and researched fracture and fatigue of PDC.…”
Section: Fig 1 Statistics On Failures Of Pdc Bit Cuttersmentioning
confidence: 99%
“…Appl et al [6] developed a new cutter wear model from the cutting experiments. Wang et al [7] established a new cutter-rock interaction model on the basis of experiments of cutting shale with PDC cutter. Kris [8] tested four different batches of PDC under monotonic and cyclic loadings, and researched fracture and fatigue of PDC.…”
Section: Fig 1 Statistics On Failures Of Pdc Bit Cuttersmentioning
confidence: 99%
“…Cutter Geometry Parameters (Back-Rake and Side-Rake Angles). Studies have demonstrated that cutting forces (vertical and cutting forces) are minimal at back-rake angles of around 15° [7,11,15,16]. In addition, specific energy and back-rake angle exhibit a nonlinear relationship.…”
Section: Introductionmentioning
confidence: 99%
“…Besides the normal force from the weight on the bit, the contact area between the cutter and rock is also dependent on the wear condition of the cutter. The effects of the cutting area on applied forces have been extensively investigated experimentally [2,3,11,16,19]. Experimental and theoretical studies were conducted to evaluate the lapping effect of the adjacent cutter on the surface area [20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…MC Jaime et al 4 established the finite element modeling of rock cutting in the drilling process. J Wang and D Zou 5 discussed the mathematical relationship between the tangential and positive forces on unit cutting area. J Zhang and J Li 6 indicated that the way of cutting rock was determined by the size of drilling pressure, and the change of rotary speed should be changed according to the physical property of coal rock.…”
Section: Introductionmentioning
confidence: 99%